GROWTH AND SURVIVAL RATE OF AFRICAN CATFISH (Clarias gariepinus) WITH THE ADDITION OF BACTERIAL INOCULANT IN BIOFLOCS TECHNOLOGY - Novrizandi Malaputra; Iskandar Putra; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from June until August 2015 at Laboratory Aquaculture of Technology University of Riau. The purpose of this research was to investigate growth and survival rate of african catfish with addition bacterial inoculant in bioflocs techniques. This research using experimental method and completely random design (RAL) with three treatment and three replications, there are P1 : every 5 days given bacterial inoculant , P2 : every 10 days given bacterial inoculant, P3 : every 15 days given bacterial inoculant . The result showed that african catfish with addition bacterial inoculant in bioflocs techniques affect significantly on the growth of absolute weight and absolute length growth but does not affect the specific growth rate and survival rate. The best treatment were obtained in treatment every 5 days given bacterial inoculant, with value growth of absolute weight 125,27 g, growth in absolute length 17,43 cm, specific growth rate 8,22% and survival rate 95,78%.Keyword : african catfish, inoculant bacteria, Bioflocs technology